The effect of surgical complications on ENT trainees. Issue 4 (26th April 2021) - McLaren, O; Perkins, C; Alderson, D
Abstract: Background: The 'second victim phenomenon' is a term attributed to the traumatic effect a medical error can have on healthcare professionals. Patient safety incidents have been shown to occur in as many as one in seven patients in hospital. These incidents cause significant, potentially devastating, trauma to patients and their relatives, and can have deep and long-lasting effects on the health professionals involved. These incidents can have a negative impact on doctors' emotional wellbeing; their professional practice in relation to this impact has not been extensively investigated in surgical trainees. Method: A survey of UK otolaryngology trainees was conducted to investigate the effects of complications and medical errors on trainees, and examine how these are discussed within departments. Results and conclusion: The findings suggest that further training is required and would be warmly received by otolaryngology trainees as part of higher surgical training.